Societal decisions about climate mitigation will have dramatic impacts on eutrophication in the 21st century - E. Sinha (Nature Portfolio, 2019)
Impacts of future changes to land use and land management on eutrophication are not well understood. Here, the authors examine these impacts over the 21st century and find that societal choices will have a huge impact on riverine total nitrogen loading for the continental United States and beyond.